1992
DOI: 10.1172/jci116076
|View full text |Cite
|
Sign up to set email alerts
|

Compartmentation of hexokinase in rat heart. A critical factor for tracer kinetic analysis of myocardial glucose metabolism.

Abstract: Radiolabeled analogues of 2-deoxyglucose are widely used to trace glucose metabolism in cell cultures, whole organs, and intact animals, although kinetic differences in transport and phosphorylation between these compounds and glucose exist. The present studies were undertaken to determine the effects of insulin stimulation on the phosphorylation of 2-deoxyglucose compared to glucose in the intact, saline-perfused working rat heart. Rates of glucose utilization determined from tritiated glucose differed from r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
33
1

Year Published

1995
1995
2003
2003

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(36 citation statements)
references
References 37 publications
2
33
1
Order By: Relevance
“…The value of the lumped constant has been measured in the hearts of rabbits (22)(23)(24) and dogs (25), and had been found to be constant over a range of insulin and glucose concentrations as well as during anoxia. However, other authors have reported variability of the lumped constant in perfused rat hearts with the addition of insulin (26,27), and have recommended that PET studies of FDG uptake in the heart should be performed under controlled metabolic conditions. For this reason, the studies here reported have been performed during steady-state conditions of hyperinsulinemia and euglycemia as realized by the insulin clamp technique.…”
Section: Discussionmentioning
confidence: 99%
“…The value of the lumped constant has been measured in the hearts of rabbits (22)(23)(24) and dogs (25), and had been found to be constant over a range of insulin and glucose concentrations as well as during anoxia. However, other authors have reported variability of the lumped constant in perfused rat hearts with the addition of insulin (26,27), and have recommended that PET studies of FDG uptake in the heart should be performed under controlled metabolic conditions. For this reason, the studies here reported have been performed during steady-state conditions of hyperinsulinemia and euglycemia as realized by the insulin clamp technique.…”
Section: Discussionmentioning
confidence: 99%
“…Hexokinase is present in the cytosolic fraction of the cell but also binds to the outer mitochondrial membrane. 23 Binding lowers the K m for glucose and increases hexokinase activity, 24 although the K m for 2-deoxyglucose remains nearly 10-fold higher than that for glucose. 24 This attachment also suppresses inhibition of hexokinase by glucose 6-phosphate.…”
Section: Hexokinasementioning
confidence: 99%
“…23 Binding lowers the K m for glucose and increases hexokinase activity, 24 although the K m for 2-deoxyglucose remains nearly 10-fold higher than that for glucose. 24 This attachment also suppresses inhibition of hexokinase by glucose 6-phosphate. 23 Insulin shifts the control strength of glucose uptake from glucose transport to phosphorylation.…”
Section: Hexokinasementioning
confidence: 99%
“…This could place hexokinase in closer apposition to the supply of glucose from glucose transporters in the membrane and could potentially increase the rate of glucose phosphorylation and uptake. In heart muscle, which primarily expresses HKII, insulin has been reported to redistribute hexokinase activity to the mitochondria (23). These investigators propose that this redistribution is important in insulin stimulation of glucose uptake.…”
Section: Discussionmentioning
confidence: 99%